2010
DOI: 10.1089/cap.2010.0018
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Risperidone and Quetiapine on Growth Parameters and Hormone Levels in Young Pigtail Macaques

Abstract: Objective: Atypical antipsychotic drugs are prescribed to young children for a number of symptoms, some with no Food and Drug Administration approval for children. Effects on growth of children have received little experimental study. We assessed the effects of two atypicals, risperidone and quetiapine, on growth, prolactin, and thyroid hormones of young pigtail macaques (macaca nemestrina), modeling potential effects on 4-8-year-old children. Methods: Subjects were studied blindly after random assignment to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…The changes in hormone levels related with risperidone treatment are also evident in animal models. In a pigtail macaque model, PRL was higher at low (0.025 mg/Kg) and high doses (0.05 mg/Kg) of risperidone during 4-month consumption, with a gradual decline until reaching placebo levels in the post-drug phase (149). In an animal model, male Wistar rats showed reduced α-MSH, agouti-related protein (AgRP), and cocaineand amphetamine-regulated transcript (CART) concentrations and increased leptin levels vs. the vehicle group after 4 weeks of treatment (2 mg/kg/day) (150).…”
Section: Risperidonementioning
confidence: 92%
“…The changes in hormone levels related with risperidone treatment are also evident in animal models. In a pigtail macaque model, PRL was higher at low (0.025 mg/Kg) and high doses (0.05 mg/Kg) of risperidone during 4-month consumption, with a gradual decline until reaching placebo levels in the post-drug phase (149). In an animal model, male Wistar rats showed reduced α-MSH, agouti-related protein (AgRP), and cocaineand amphetamine-regulated transcript (CART) concentrations and increased leptin levels vs. the vehicle group after 4 weeks of treatment (2 mg/kg/day) (150).…”
Section: Risperidonementioning
confidence: 92%
“…It follows from this that people taking antipsychotic drugs are likely to be at increased risk of osteoporosis. Recent animal studies in macaques and rats have found that antipsychotic treatment was associated with reduced bone mineralisation (Sackett et al , ; Kunimatsu et al , ). In the rat study, the significant reductions in femoral BMD were linked to the effects of prolactin elevation and decreased oestradiol levels during antipsychotic treatment (Kunimatsu et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, atypical antipsychotic drugs with less severe side effects have been used in pediatric clinical treatment but the safety and efficacy of these drugs for children and adolescents has not been well-established. A project at the IPRL was undertaken to evaluate the effects of two drugs in this class, risperidone and quetiapine , in young, normally developing male Macaca nemestrina monkeys [Sackett et al, 2010]. Males received a daily dose of risperidone (0.25 mg/kg) or quetiapine (2 mg/kg) for 4 months.…”
Section: Research In Reproductive and Developmental Sciences At The Iprlmentioning
confidence: 99%
“…Recently, atypical antipsychotic drugs with less severe side effects have been used in pediatric clinical treatment but the safety and efficacy of these drugs has not been well established. A project at the IPRL was undertaken to evaluate the effects of two drugs in this class, risperidone and quetiapine, in young, normally developing male M. nemestrina monkeys [Sackett et al, 2010]. Subjects were tested on a comprehensive developmental test battery that included measures of (1) social, cognitive, emotional, perceptual and motor behavior; (2) physical assessments of health, somatic growth, bone mineralization, and hormonal function; and (3) highresolution anatomical and chemical magnetic resonance brain imaging.…”
Section: Neuroleptic Drugsmentioning
confidence: 99%